2005
DOI: 10.1158/0008-5472.can-05-2352
|View full text |Cite
|
Sign up to set email alerts
|

A Polycistronic MicroRNA Cluster, miR-17-92, Is Overexpressed in Human Lung Cancers and Enhances Cell Proliferation

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs, thought to be involved in physiologic and developmental processes by negatively regulating expression of target genes. We have previously reported frequent down-regulation of the let-7 miRNA family in lung cancers and, in the present study, assessed alteration in a panel of 19 lung cancer cell lines. As a result, we found for the first time that the miR-17-92 cluster, which comprises seven miRNAs and resides in intron 3 of the C13or f 25 gene at 13q31.3, is markedly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
1,134
6
19

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,457 publications
(1,187 citation statements)
references
References 18 publications
28
1,134
6
19
Order By: Relevance
“…MiR‐18 is expressed widely throughout the body, while expression of miR‐124a is restricted to the brain. In small cell lung cancer, reduced GR levels have been associated with GC resistance, which might be caused by miR‐18 up‐regulation 18, 19. We found that expression levels of miR‐18a in PBMCs were positively correlated with cortisol, CRH and IL‐6.…”
Section: Discussionmentioning
confidence: 73%
“…MiR‐18 is expressed widely throughout the body, while expression of miR‐124a is restricted to the brain. In small cell lung cancer, reduced GR levels have been associated with GC resistance, which might be caused by miR‐18 up‐regulation 18, 19. We found that expression levels of miR‐18a in PBMCs were positively correlated with cortisol, CRH and IL‐6.…”
Section: Discussionmentioning
confidence: 73%
“…Overexpression of the miR‐17‐92 cluster is observed in a variety of cancers, including small‐cell lung cancer, colon cancer, neuroblastomas, medulloblastoma and gastric cancer 35, 36, 37, 38. Calvano et al .…”
Section: Resultsmentioning
confidence: 99%
“…The miR-17-92 cluster is frequently amplified in several lymphomas and in lung cancer, 16,42 and aberrant overexpression of the miR-17-92 polycistron is detected in many cancers. 43 Retinoblastoma-like 2 protein (p130, Rbl2), Cdk inhibitor p21CIP1, transforming growth factor β1 (TGFβ1), proapoptotic Bcl-2 protein Bim, the tumor-suppressor PTEN and transcription factor E2F1 are some of the cluster's targets.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Also known as oncomir-1, the cluster enhances cell proliferation or inhibits apoptosis by suppressing targets such as Bim, E2F1 and PTEN and is markedly overexpressed in human cancers. [15][16][17][18][19][20][21] Reduced levels of PHLPP2 in chemoresistant miR-17-92 overexpressing mantle cell lymphomas had suggested that the phosphatase could be a target of oncomir-1. 12 Known major activators of the miR-17-92 cluster are transcription factor c-MYC and members of the E2F family, whereas p53 acts as a repressor under hypoxic conditions.…”
mentioning
confidence: 99%